2015
DOI: 10.1371/journal.pone.0142455
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Cadmium, Placental Permeability and Birth Outcomes in Coastal Populations of South Africa

Abstract: BackgroundThe impact of prenatal exposure to cadmium (Cd) on birth outcomes is an area of concern. This study aimed to assess an impact of prenatal Cd exposure on birth outcomes in distinct coastal populations of South Africa.MethodsCadmium was measured in maternal blood (CdB) (n = 641), cord blood and in maternal urine (n = 317). This investigation assessed the associations between CdB (non-transformed) and birth outcomes across the 25th, 50th, and 75th percentile for birth weight, birth length and head circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 33 publications
1
22
1
2
Order By: Relevance
“…This was first proposed by Kippler et al 20, 21. in a cohort in Bangladesh and has subsequently been replicated in cohorts from South Africa and the USA 8, 19. Kippler et al 20.…”
Section: Commentsmentioning
confidence: 87%
See 3 more Smart Citations
“…This was first proposed by Kippler et al 20, 21. in a cohort in Bangladesh and has subsequently been replicated in cohorts from South Africa and the USA 8, 19. Kippler et al 20.…”
Section: Commentsmentioning
confidence: 87%
“…This was first proposed by Kippler et al 20,21 in a cohort in Bangladesh and has subsequently been replicated in cohorts from South Africa and the USA. 8,19 Kippler et al 20 suggested several mechanisms for this differential effect: (1) the relative sensitivity of female fetuses compared with male fetuses to a Cd-induced increase in glucocorticoid concentrations reflecting a decrease in 11b-HSD2 activity, with a consequent increase in cortisol level; (2) differential Cd interference with the IGF axis, as there is some evidence that levels of IGF subtypes are sex-specific; (3) the male skeleton may be more resistant to Cd-induced bone damage through differential effects on bone mineralization, bone density, and bone mineral content; (4) there may be effects on in utero sex-specific programming that contribute to the vulnerability of the fetus to environmental stressors. As suggested by Rollin et al 8 these effects may be related to hypomethylation of growth-related genes in girls relative to hypermethylation in boys in response to Cd exposure.…”
Section: Commentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Проникання лікарських засобів від матері до плода залежить від структури плаценти, Cd в популяціях тварин -від його дородової експозиції (Röllin et al, 2015), у людей -від статевих і вікових відмінностей (Walker et al, 2017). Оцінка проникності Cd взаємозв'язана з статусом гемоглобіну (Bonglaisin et al, 2017) і наявності наночасток, які впливають на проникність плацентарного бар'єра (Muoth еt al., 2015), що узгоджується з отриманими результатами при моделюванні запальних реакцій у відповідь на бактеріальну інфекцію (Sanders еt al., 2015;Qin et al, 2018).…”
Section: вступunclassified